Coupling UiO-66 MOF with a Nanotubular Oxide Layer Grown on Ti-W Alloy Accelerates the Degradation of Hormones in Real Water Matrices - Disigant, Isabela [UNESP]; de Almeida, Juliana [UNESP]; Okamoto, Débora Noma; Bertazzoli, Rodnei [UNESP]; de Arruda Rodrigues, Christiane [UNESP] (American Chemical Society (ACS), 2024)
To enable the photoelectrocatalytic treatment of large volumes of water containing low concentrations of pollutants, this study introduces a hybrid photocatalyst, composed of nanotubular oxides grown on TixW alloy (x = 0.5 and 5.0 wt %) modified with UiO-66 MOF, for degradation of estrone (E1) and 17α-ethinyl estradiol (EE2). The oxide layer (Nt/TixW) was prepared via anodization, while UiO-66 nanoparticles were synthesized by using a solvothermal process. Different techniques for modifying nanotubular oxides were evaluated to maximize the photocatalytic activity and the sorption process. In photo(electro)catalytic experiments using low concentrations of E1 and EE2 synthetic solutions and UV-vis radiation (100 W/cm2), all modified materials exhibited approximately 40% higher degradation compared to the unmodified photocatalyst, keeping the same sequential performance of the photocatalysts (Nt/TiO2 < Nt/Ti-0.5W < Nt/Ti-5.0W) independent of the treatment. This enhancement was attributed to the MOF’s increased hormone sorption, with no synergistic interaction observed between the photocatalyst and the adsorbent. In real water supply matrices, the photoelectrocatalytic removal rate of E1 using Nt/Ti-5.0W modified UiO-66 under UV-vis radiation and 1.3 V was 0.168 s-1, while for EE2, it was 0.310 min-1, approximately 1.78 and 18.21 times faster than obtained with the unmodified photocatalyst. The slower degradation rate of EE2 compared to that of E1 is attributed to the formation of denser intermediates that compete with smaller organic molecules in the real matrix. The cooperative effect between NT/TixW and UiO-66 favored the confinement of pollutants and by-products within the UiO-66 cavity, minimizing the diffusion effects and promoting the degradation of these compounds by the OH· radical generated at the oxide/solution interface. Among the tested electrodes, NT/Ti5W modified with UiO-66 demonstrated the highest efficiency and stability during the recycle tests. This highlights its promise for applications in photocatalytic processes for treating water supplies with low pollutant concentrations.